Transcriptome Analysis of Oleoresin-Producing Tree Sindora Glabra and Characterization of Sesquiterpene Synthases - Yu, Niu; Yang, Jin-Chang; Yin, Guang-Tian; Li, Rong-Sheng; Zou, Wen-Tao (Frontiers in Plant Science, 2018)
Terpenes serve important physiological and ecological functions in plants. Sindora glabra tree accumulated copious amount of sesquiterpene-dominant oleoresin in stem. Transcriptome approach was used to discover the unique terpene biosynthesis pathway and explore the different regulatory mechanism responsible for the variation of terpene content among individuals. Analysis of de novo assembled contigs revealed complete set of genes for terpene biosynthesis. A total of 23,261 differentially expressed unigenes (DEGs) were discovered between high and low oil-yielding plants. DEGs enrichment analysis suggested that terpene biosynthesis process and plant hormone signal transduction pathway may exert the major role in determining terpene variation in S. glabra. The expression patterns of candidate genes were further verified by quantitative RT-PCR experiments. Key genes involved in terpene biosynthesis pathway were predominantly expressed in phloem and root tissues. Phylogenetic analysis and subcellular localization implicated S. glabra terpene synthases may evolve from an common ancestor. Furthermore, two sesquiterpene synthase genes SgSTPS1 and SgSTPS2 were functionally characterized. SgSTPS1 mainly generated β-caryophyllene from farnesyl pyrophosphate. SgSTPS2 was a versatile enzyme that catalyzed the formation of twelve sequiterpenes from farnesyl pyrophosphate and synthesis of three monoterpenes using geranyl pyrophosphate. Together, these provide huge reservoir for elucidating the molecular mechanism of terpene biosynthesis and exploring the ecological function of sesquiterpenes in S. glabra.